2023
DOI: 10.1177/23969415231179844
|View full text |Cite
|
Sign up to set email alerts
|

Behaviors related to autism spectrum disorder in children with developmental language disorder and children with 22q11.2 deletion syndrome

Abstract: Background and Aim. Children with Developmental Language Disorder (DLD) are at an increased risk to develop behaviors associated with Autism Spectrum Disorder (ASD). The relationship between early language difficulties and the occurrence of ASD-related behaviors in DLD is poorly understood. One factor that may hinder progress in understanding this relationship is the etiological heterogeneity of DLD. We therefore study this relationship in an etiologically homogeneous group of children, who share phenotypic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…A previous study showed that weaker receptive language abilities in children with 22q11DS are associated with increased behavioral problems in social communication and interaction [36]. In the literature, there are opposing data regarding the receptive language skills of patients with 22q11.2DS.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that weaker receptive language abilities in children with 22q11DS are associated with increased behavioral problems in social communication and interaction [36]. In the literature, there are opposing data regarding the receptive language skills of patients with 22q11.2DS.…”
Section: Discussionmentioning
confidence: 99%